Clinical, histopathological, and serological comparisons between primary and secondary Sjögren’s Syndrome - Mustafa, Nazih Shaban; Kummoona, Raja; Osami, Mohammed H AL; Rawi, Ziad S. AL (2024)
Abstract: This study compares the clinical, serological, and histopathological characteristics of primary Sjögren's Syndrome (pSS) and secondary Sjögren's Syndrome (sSS) in Iraqi patients. Conducted at Medical City Hospital / Baghdad over two years, it enrolled 218 pSS and 207 sSS patients. Key findings include significant differences in parotid gland enlargement, arthritis, and serological markers between the groups. These results highlight the distinct clinical profiles of pSS and sSS, contributing to better diagnostic and treatment approaches.Sjogren’s syndrome, primary Sjogren’s syndrome, secondary Sjogren’s syndrome, parotid gland enlargement, autoimmune disease